PPARɑ variant V227A reduces plasma triglycerides through enhanced lipoprotein lipolysis - Lauren F. Uchiyama; Gabriel P.M. Ordonez; Khoi T. Pham; John P. Kennelly; Maykel López Rodríguez; Lany Tran; Peter Tontonoz; Alexander Nguyen (Journal of Lipid Research)
Human single nucleotide variants in peroxisome proliferator-activated receptor-ɑ (PPARɑ) have been associated with beneficial metabolic phenotypes, yet their specific effects on metabolic gene expression are not well defined. Here, we developed a mouse model of a human PPARɑ variant encoding a substitution of valine for alanine at position 227 (V227A) to explore the role of this variant on systemic metabolism. Substitution with this variant in mice reduced plasma triglycerides, without altering body mass or liver lipid accumulation, consistent with phenotypes observed in human cohorts. Gene expression analysis revealed that the V227A variant enhances Ppara target gene expression in mouse liver, consistent with the effects of synthetic PPARɑ agonist treatment. Notably, V227A increased hepatic expression of Lpl, the predominant enzyme responsible for circulating triglyceride hydrolysis. Further characterization revealed that heart tissue from variant mice exhibited increased Lpl expression and triglyceride hydrolysis activity, suggesting that V227A enhances cardiac triglyceride clearance. These findings validate human observational studies and clarify the physiological impact of the V227A PPARɑ variant on plasma triglycerides.